'It's just another thing to think about': encouraging students' engagement in extracurricular activities. Issue 6 (3rd July 2021) - Dickinson, Jill; Griffiths, Teri-Lisa; Bredice, Alex
ABSTRACT: Against the backdrop of a diverse and challenging Higher Education (HE) environment within the United Kingdom (UK), this paper extends existing debates around extracurricular activities (ECAs) and considers students' engagement in ECAs within this context. Adopting a case study approach, and involving a team of student researchers, students' perceptions of ECA-programmes at a post-1992 Higher Education Institution (HEI) are explored. A total of 38 students took part in a series of six focus groups. The data collected was thematically analysed and two key themes emerged, namely: perceptions that there is a hierarchy of ECAs, and an enhanced awareness of the barriers to students' participation in ECAs, including the potential for harm. This paper examines the prospective impact of these findings and makes recommendations for the future development of ECA-programmes within HEIs.